Developmental staging table of the green iguana - Lima, Fabiano C.; Py-Daniel, Taina R.; Sartori, Marina R.; Abe, Augusto S. [UNESP]; Santos, Odeony Paulo dos; Freitas, Leticia M.; Pereira, Kleber F.; Sebben, Antonio (Wiley-Blackwell, 2019)
Embryonic staging tables provide information to standardize embryological investigations and to subsidize discussions about evolution. We have established a developmental staging table for Iguana iguana iguana. The sample was composed of 142 embryos, incubated at a constant temperature and collected at regular intervals. Morphological features as pharyngeal arches, craniofacial structures, eyes, limbs, claws, pigmentation, scales and egg tooth were evaluated to determine development stages. The normal staging table includes 17 stages from oviposition to hatching, based on chronology and morphological external features. Stages from 1 to 27 occur before oviposition. Stage 28 was the first described, because all embryos presented limb bud anlage, key feature of the previous stage. We used pharyngeal arches and limb buds to describe the first stages; claws, genital papilla and scales to describe the middle stages; and pigmentation, size and egg tooth to describe the last stages. Incubation lasted approximately 2 months in a controlled environment. The results were similar to the data from other lizards, confirming the embryonic conservative pattern of the group.
Keywords: development; embryos; lizard; squamata